TANGGUNG JAWAB GURU TERHADAP KESUKSESAN BELAJAR SISWA. - Dorlan Naibaho; Sadima pasaribu (JURNAL ILMIAH NUSANTARA, 2025)
Lack of understanding of children's learning can be caused by several factors. One of them is that the lack of teachers' role in the learning process at school can cause children's understanding to decrease. Teachers have a big responsibility for the continuity of the learning process at school. Whether we realize it or not, we see that apart from equipment and everything else related to educational success and educational goals, it is the teacher's personality that determines the success of learning. So that there is no indifference and forced obedience from students, teachers need to continue to improve their personal abilities and how to be learning partners for their students and develop good character so that they can become role models for their students. Teachers should set an example for their students. student. This will motivate teachers to want to learn.